Analysis of Factors Leading to Students’ Entrepreneurial Intention: A Literature Review - Hizbul Khootimah Azzaakiyyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Finding a job for university graduates is becoming increasingly difficult, and the number of job opportunities available is not proportional to the number of graduates or new labor supply at all levels of education. This condition requires students to think more imaginatively in order to find opportunities and avoid unemployment, because the more developed a country is, the more educated its people are, and the greater the need for entrepreneurship. The purpose of this study is to analyze and provide evidence that there are crucial elements that influence students' entrepreneurial intentions. This literature review article develops a conceptual framework on college students' entrepreneurial intention based on the constructs of entrepreneurship education, peers, mindset, self-efficacy, creativity, attitude towards entrepreneurship, social media, entrepreneurial culture, and motivation are the elements that influence college students' entrepreneurial intention. According to the literature review, the nine latent constructs can be a benchmark for students in creating entrepreneurial intention. This study's research methodology and accompanying arguments can help advance the discussion in the subject of business management and administration. This research has important implications for future studies that use quantitative, qualitative, and mixed methodologies.